Pregnancy Rate in Synchronized Iraqi Awassi Ewes Inseminated Artificially and Naturally - Abas, H. Kassem; Alyasiri E.A; Al-Hamedawi; T.M., Hmod M. Ajeel (Institute of Medico-legal Publications Pvt Ltd, 2022)
This study was carried out to evaluate the efficacy of imported Australian frozen semen straws inachieving successful artificial insemination program in estrus synchronized ewes. This study conductedon twenty-one Awassi ewes, aged 2 - 4 years, and four fertile rams (two rams for natural mating and twofor detecting of estrous by using apron) in Baghdad province (Rumintia Research station, departmentof animal resource research, state Board for Agriculture Research, Ministry of Agriculture/ AbuGhraib district), for the period from November 2020 to March 2021. Pregnancy diagnosis was doneby ultrasound to detect reproductive status of the ewes, then all non-pregnant ewes were synchronizedby using vaginal sponges (60 mg of Medroxy acetate Progesterone / MAP) for 10days plus 500IU ofPregnant Mare Serum Gonadotropin (PMSG) in day 10, all animals were divided randomly into threeequal groups each of seven ewes according to the type of insemination, G1 (1straw) and G2 (2 straws/8 hrs. interval) and G3 serviced naturally by fertile rams then the females were isolated from the males.The response of animals to hormonal treatment was 21, with a response rate of 100% in all groups withno significant difference with mean durations of response recorded 63.6± 11.7, 66.7± 12.2, and 62.8±10.7 for the three groups, respectively. The pregnancy rate with single, double AI and natural matingwas 41.86 and 71.41 and 71.42 percent, respectively with a highly significant difference (P<0.01)between G1 and G2. In conclusion, under field conditions, double AI with 20 ×106 sperm proved to besuitable for generating high pregnancy rates in Iraqi Awassi ewes.